The benefits of automated dispensing machine for hospital pharmacy in Indonesia: situation, implementation, and feasibility - Suryadinata, Haryman Utama (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Pharmacy as the main core of hospital is responsible for the quality and safety of medicines. Yet the numbers of medication errors are still high. Automated Dispensing Machine (ADM) is one of the solutions to reduce the dispensing errors in pharmacy. Many countries had studied and proved that the use of ADM gives more benefit than liability. However, ADM is considered as something new, a